Velvet. volume 2, The secret lives of dead men - Brubaker, Ed (The secret lives of dead men, 2015)
"Everything Velvet Templeton ever believed about the worst night of her life has turned out to be a lie, and now she's coming back to London, taking the hunt back to the hunters, to find the truth or die trying!"--Page 4 of cover.